1999
DOI: 10.1074/jbc.274.43.31000
|View full text |Cite
|
Sign up to set email alerts
|

Role of Factor VIII C2 Domain in Factor VIII Binding to Factor Xa

Abstract: Factor VIII (FVIII) 1 is a glycoprotein cofactor that accelerates the generation of factor Xa (FXa) by factor IXa in the presence of Ca 2ϩ and negatively charged phospholipid (PL) expressed on a membrane surface (1). Quantitative and qualitative deficiencies of FVIII result in the congenital bleeding disorder, hemophilia A. FVIII is noncovalently bound to von Willebrand factor (vWF) in plasma. vWF regulates the synthesis, the cofactor activity, and the transport of FVIII to the site of vascular injury (2-4).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 43 publications
1
74
1
Order By: Relevance
“…Recently, a factor Xa-interactive site has been identified in the C2 domain by analyses including antibody inhibition and anhydro-factor Xa binding assays (16). Results presented in that study showed the C2 domain-specific antibody completely blocked factor Xa-catalyzed cleavages in the factor VIII light chain (at Arg 1689 and Arg 1721 ) while only partially blocking cleavage of the heavy chain (at Arg 372 ).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Recently, a factor Xa-interactive site has been identified in the C2 domain by analyses including antibody inhibition and anhydro-factor Xa binding assays (16). Results presented in that study showed the C2 domain-specific antibody completely blocked factor Xa-catalyzed cleavages in the factor VIII light chain (at Arg 1689 and Arg 1721 ) while only partially blocking cleavage of the heavy chain (at Arg 372 ).…”
Section: Discussionmentioning
confidence: 64%
“…A factor Xa-interactive site required for cofactor activation has been mapped within the residues 2253-2270 of the C2 domain of factor VIII (16). Furthermore, factor VIII alloantibody inhibitors recognizing this epitope within the C2 domain inhibit factor Xa-catalyzed factor VIII activation by directly blocking the interaction between the factor VIII and factor Xa (17).…”
Section: From the Departments Of ‡Biochemistry And Biophysics And ¶Mementioning
confidence: 99%
See 1 more Smart Citation
“…FVIII binding to anhydro-thrombin in the current investigations was also not affected by the presence of vWF or PL (data not shown), suggesting that the thrombin-binding site in the C2 domain is separated from the vWF-and PL-binding sites. In our previous work (20) we identified the FXa-binding site within the C2 domain, and we demonstrated that binding of FXa was completely inhibited by the presence of the vWF. This is markedly in contrast to the binding profile of thrombin demonstrated in the current study.…”
Section: Competitive Inhibition Of Thrombin Proteolysis Of Lch Bymentioning
confidence: 99%
“…Binding in this domain appears to be competitive and mutually exclusive (4,5,8,9). The C2 domain has also been shown to participate in binding to factor Xa and thrombin (10,11). Additionally, a major epitope for allo-and autoantibodies and for monoclonal antibodies has been located within the C2 domain (4,6,12), indicating that this region could be an antigenic "hot spot."…”
mentioning
confidence: 99%